Antibacterial Activity Of Some Essential Oils Against Food Borne Pathogen And Food Spoilage Bacteria - PATIL SAHADEO D.; KAMBLE VILAS A. (International Journal of Pharma and Bio Sciences, 2011)
Essential oils are well known in traditional medicine as antiseptic and antimicrobial agents. This study determined the antimicrobial effects of eleven spice essential oils using a disc diffusion method against four Gram-positive and eight Gram-negative bacteria of spoilage and health significance. Cassia oil showed the largest zones of inhibition (12 to 54 mm) and the widest antibacterial spectrum, followed by essential oil of allspice, clove and nutmeg. Essential oils of mace, celery, ginger, cardamom, black pepper, fennel and turmeric were the least effective spice oils. Gram-positive bacteria were shown to be more sensitive to the spice essential oils than Gram-negative bacteria. Staphylococcus aureus and Bacillus subtilis were the most sensitive bacterial strains tested; where as a strain of Escherichia coli (MTCC-118) was the least sensitive. These results showed that spice essential oils may prove useful in inhibiting bacteria of food spoilage and health significance.